Associations of Perfluoroalkyl substances with blood lipids and Apolipoproteins in lipoprotein subspecies: the POUNDS-lost study - Gang Liu; Bo Zhang; Yang Hu; Jennifer Rood; Liming Liang; Lu Qi; George A. Bray; Lilian DeJonge; Brent Coull; Philippe Grandjean; Jeremy D. Furtado; Qi Sun (BMC, 2020)
Abstract Background The associations of perfluoroalkyl substance (PFAS) exposure with blood lipids and lipoproteins are inconsistent, and existing studies did not account for metabolic heterogeneity of lipoprotein subspecies. This study aimed to examine the associations between plasma PFAS concentrations and lipoprotein and apolipoprotein subspecies. Methods The study included 326 men and women from the 2-year Prevention of Obesity Using Novel Dietary Strategies (POUNDS) Lost randomized trial. Five PFASs, including perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA), perfluorohexanesulfonic acid (PFHxS), perfluorononanoic acid (PFNA), and perfluorodecanoic acid (PFDA), were measured in plasma at baseline. For lipoprotein and apolipoprotein subspecies, total plasma was fractionated first by apolipoprotein (apo) C-III content and then by density. Each subfraction was then measured for apoB, apoC-III, and apoE concentrations, as well as triglyceride and cholesterol contents, both at baseline and at 2 years. Results For lipids and apolipoproteins in total plasma at baseline, elevated plasma PFAS concentrations were significantly associated with higher apoB and apoC-III concentrations, but not with total cholesterol or triglycerides. After multivariate adjustment of lifestyle factors, lipid-lowering medication use, and dietary intervention groups, PFAS concentrations were primarily associated with lipids or apolipoprotein concentrations in intermediate-to-low density lipoprotein (IDL + LDL) and high-density lipoprotein (HDL) that contain apoC-III. Comparing the highest and lowest tertiles of PFOA, the least-square means (SE) (mg/dl) were 4.16 (0.4) vs 3.47 (0.4) for apoB (P trend = 0.04), 2.03 (0.2) vs 1.66 (0.2) for apoC-III (P trend = 0.04), and 8.4 (0.8) vs 6.8 (0.8) for triglycerides (P trend = 0.03) in IDL + LDL fraction that contains apoC-III. For HDL that contains apoC-III, comparing the highest and lowest tertiles of PFOA, the least-square means (SE) (mg/dl) of apoC-III were 11.9 (0.7) vs 10.4 (0.7) (P trend = 0.01). In addition, elevated PFNA and PFDA concentrations were also significantly associated with higher concentrations of apoE in HDL that contains apoC-III (P trend< 0.01). Similar patterns of associations were demonstrated between baseline PFAS concentrations and lipoprotein subspecies measured at 2 years. Baseline PFAS levels were not associated with changes in lipoprotein subspecies during the intervention. Conclusions Our results suggest that plasma PFAS concentrations are primarily associated with blood lipids and apolipoproteins in subspecies of IDL, LDL, and HDL that contain apoC-III, which are associated with elevated cardiovascular risk in epidemiological studies. Future studies of PFAS-associated cardiovascular risk should focus on lipid subfractions.